Surgical Outcomes of Pseudoexfoliation Syndrome among the Indian Rural Population Scheduled for Small Incision Cataract Surgery: A Prospective Interventional Study - Rutviben Ravjibhai Sadatia; Nisha Ahuja; Vegada Bhavisha; Raghunathan Iodine; Kurian Abraham (International Journal of Anatomy Radiology and Surgery, 2022)
Introduction: Pseudoexfoliation (PXF) syndrome is an age related systemic disorder with primary ocular manifestations characterised by PXF deposits and changes in tissues of anterior segment which make cataract operations potentially challenging. Aim: To analyse surgical outcomes of Small Incision Cataract Surgery (SICS) on eyes with PXF, compared with eyes without PXF. Materials and Methods: This prospective interventional study was conducted between August 2015 to June 2016 on each eye of 100 patients who attended free eye camps in rural areas of Western India and underwent SICS. Two groups were formed: group A both males and females of age 50 years or more who had cataract with non glaucomatous PXF (n=50); group B both males and females with age 50 years or more who had cataract without PXF (n=50). Detailed history and slit lamp examinations were done. All the patients were operated upon by the same surgeon. Surgical outcomes assessed were incidence of intraoperative complications, postoperative complications and visual outcomes. Intraoperative difficulties experienced by surgeon like inadequate pupillary dilatation, phacodonesis, zonular dialysis, posterior capsular rupture, vitreous loss etc., were reported. Postoperative findings of visual acuity, Intraocular Pressure (IOP) and slit lamp evaluation {corneal oedema, anterior chamber inflammation, retained lens matter, hyphema, Intraocular Lens (IOL) centration} on day one and one month were analysed. Comparative analysis of surgical outcomes was done between the two groups by using the Mann-Whitney U test and Fisher’s exact test. Results: The mean age of the patients was 62.48 (±5.62) years in the PXF group and 60.7 (±7.63) years in the without PXF group (p=0.1870). Most frequent encountered complication was inadequate pupillary dilatation in PXF group. There was no statistically significant difference in intraoperative complications (zonular dialysis) between the two groups (p=0.4949). Postoperatively, corneal oedema and raised IOP were more in PXF group on postoperative day one compared to group without PXF (p=0.0167, p=0.0226). In both groups, there were no corneal oedema and raised IOP postoperatively at one month follow-up. Both groups had improved visual acuity with no statistical difference at one month follow-up (p=0.5892). Conclusion: Eyes with PXF undergoing SICS are not associated with a higher rate of surgical complications in our study, however, it requires proper preoperative assessment and intraoperative care to ensure optimal surgical outcomes. In PXF syndrome, more time is required to attain maximal visual acuity in comparison with non PXF patients.